Information Technology and Systems Proceedings of ICITS 2019 - Rocha, Álvaro; Ferrás, Carlos; Paredes, Manolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features a selection of articles from The 2019 International Conference on Information Technology & Systems (ICITS'19), held at the Universidad de Las Fuerzas Armadas, in Quito, Ecuador, on 6th to 8th February 2019. ICIST is a global forum for researchers and practitioners to present and discuss recent findings and innovations, current trends, professional experiences and challenges of modern information technology and systems research, together with their technological development and applications. The main topics covered are: information and knowledge management; organizational models and information systems; software and systems modeling; software systems, architectures, applications and tools; multimedia systems and applications; computer networks, mobility and pervasive systems; intelligent and decision support systems; big data analytics and applications; human-computer interaction; ethics, computers & security; health informatics; information technologies in education; cybersecurity and cyber-defense; electromagnetics, sensors and antennas for security.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence